ANALISIS DEIKSIS SOSIAL PADA CERPEN SENYUM KARYAMIN KARYA AHMAD TOHARI - Prasakti, Fransiska Pratiwi (Universitas Lampung, 2024)
Deixis is a type of language, either words or phrases, which functions as a pointer for certain things or functions outside of language. This research aims to study the use of social deixis, especially in mentioning titles, nicknames, professions and positions in Ahmad Tohari's prose literary work,